Gestão e gerenciamento de resíduos de equipamentos eletrônicos: o campus central da UFRN em análise - Carvalho, Dacifran Cavalcanti (2015)
The intense socioeconomic changes that occurred in the late 1970s, arising from the process of internationalization of the economy, boosted the production and consumption of electronic equipments all over the world. As a result, there was an increase in demand for natural resources for their manufacturing, and a greater quantity and variety of wastes were being generated and deposited inappropriately on Earth, leading to the degradation of the environment. This context imposes a new challenge to the Educational Institutions of Higher Education (EIHE)1: manage and administrate in an environmentally sustainable manner their Electronic Equipment Waste (EEW)2. This study approaches the theme through the perspective of an analysis of the interaction between the Environmental Agenda in Public Administration and the Solid Waste National Policy and their contributions to sustainable practices, having as reference the Central Campus of the Federal University of Rio Grande do Norte (UFRN), considering their management and administration system of the EEW generated there. The study provides the evidences of the interaction and contribution of both those milestones for the practice of sustainable actions in management and administration of solid wastes, including the social, economical and environmental dimension, demonstrating that the long way to go in support of the sustainable development does not disqualify the contributions of these instruments to the institutions that start to use them. Methodologically, the investigation was guided by a bibliographical, documentary and field research. To the intended observation, we have done the research using case study and qualitative and quantitative exploratory research. It is a local context which has a global dimension, because the environmental degradation resulting from excessive consumption of electronic equipments and inadequate disposal of the EEW represents a phenomenon that affects significantly and negatively the quality of the ecosystem, the safety and the health of the inhabitants of the Earth. The research results indicate that the storage conditions of the EEW, as well as the process of collecting the sample units is inadequate; there is no requirement of showing the Certification of Environmental Sustainable Final Disposal of the EEW by the participants in the battling bidding, both in the public notice, by the Permanent Commission of Bidding, as in the time of gathering the EEW, by the Department of Material and Patrimony; and that there is the lack of a center for sorting and recovery of such waste, competent staff and adequate tools for the effectiveness of this process. These results also detect lacks in the politics, advocated by A3P and PNRS, to encourage the processes of reduction, reuse and recycling. So, it suggests measures that have already been applied in a similar case at another Public Institution in order to mitigate the problems arising from the inadequate management and administration of the EEW.